2013
DOI: 10.4097/kjae.2013.65.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Current practice in hemodynamic monitoring and management in high-risk surgery patients: a national survey of Korean anesthesiologists

Abstract: BackgroundHemodynamic optimization improves postoperative outcomes in high-risk surgery patients. The monitoring of cardiac output (CO) and dynamic parameters of fluid responsiveness can guide hemodynamic optimization. We conducted a survey to assess the current hemodynamic monitoring and management practices of Korean anesthesiologists during high-risk surgery.MethodsE-mails containing a link to our survey, which consisted of 33 questions relating to hemodynamic monitoring during high-risk surgery, were sent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Though this result agrees with that obtained in similar studies conducted among Korean, Chinese, American, and European anesthetists,[ 2 4 6 ] we observed a huge gap in the usage of these two monitoring devices in this survey. The reasons responsible for low application of the cardiac output monitoring in other studies include the fact that some believe that cardiac output maximization is unnecessary or may be harmful[ 7 8 ] and that the procedure is difficult to perform routinely in the busy operating room.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Though this result agrees with that obtained in similar studies conducted among Korean, Chinese, American, and European anesthetists,[ 2 4 6 ] we observed a huge gap in the usage of these two monitoring devices in this survey. The reasons responsible for low application of the cardiac output monitoring in other studies include the fact that some believe that cardiac output maximization is unnecessary or may be harmful[ 7 8 ] and that the procedure is difficult to perform routinely in the busy operating room.…”
Section: Discussionsupporting
confidence: 92%
“…This “addiction” to CVP by many clinicians despite studies that have shown its inadequate predictability of fluid responsiveness[ 5 9 ] has been documented by many other authors. [ 2 4 6 ] This has been attributed to familiarity with traditional variables and unavailability of standard protocols for cardiac output optimization. [ 4 ] Considering available HM tools available in Nigeria, central venous monitoring appears to be an important tool and may represent the peak device for assessing fluid responsiveness among high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of data offered by recent studies suggests that inspite of minor limitations, changes in arterial pressure track blood flow changes accurately, following a fluid challenge. [ 12 16 17 18 19 ] Thus, we opted to use an arterial pressure-based variable, DD for determining fluid responsiveness. Prior studies done in perioperative and ICU populations using DD showed that a cutoff of 5 mmHg can be used for differentiating fluid responders from NR and can also be used to diagnose hypovolemia and initiate fluid loading.…”
Section: Discussionmentioning
confidence: 99%
“…From 368 respondents, 35 % routinely monitored cardiac output with similar numbers in Europe and in North America [ 6 ]. A similar survey of members of the Korean Society of Anesthesiologists revealed that 59 % of 139 respondents were using cardiac output monitoring [ 8 ]. The findings of a paper-based survey of Chinese anaesthetists showed that cardiac output monitoring was used by 13 % of 210 respondents [ 9 ].…”
Section: Discussionmentioning
confidence: 99%